Conjugate Hydrocyanation of Aromatic Enones Using Potassium Hexacyanoferrate(II) as an Eco-Friendly Cyanide Source - Li, Zheng; Liu, Chenhui; Zhang, Yupeng; Li, Rongzhi; Ma, Ben; Yang, Jingya (Synlett, 2012)
A selective conjugate hydrocyanation of aromatic enones by a one-pot, two-step procedure using potassium hexacyanoferrate(II) as an original eco-friendly cyanide source, potassium hydroxide as a base, and benzoyl chloride as a promoter was described. This protocol has the advantages of a nontoxic cyanide source, high yield, and simple workup procedure.
Keywords: conjugate hydrocyanation; 1,4-addition; aromatic enone; green chemistry; nucleophilic addition; potassium hexacyanoferrate(II)